2015
DOI: 10.1103/physrevlett.114.108102
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Upstream Swimming via a Hydrodynamic Transition

Abstract: We demonstrate that upstream swimming of sperm emerges via an orientation disorder-order transition. The order parameter, the average orientation of the sperm head against the flow, follows a 0.5 power law with the deviation from the critical flow shear rate (γ − γc). This transition is successfully explained by a hydrodynamic bifurcation theory, which extends the sperm upstream swimming to a broad class of near surface micro-swimmers that possess front-back asymmetry and circular motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 42 publications
3
104
0
Order By: Relevance
“…Sperm motility behaviors were robust, as little variability was seen across samples from three different bulls. We reported in a previous publication that the chiral trajectories are caused by the near-surface resistive force exerted on the sperm head (11). Chiral swimming trajectories are characteristics of all near-surface pusher microswimmers (16,17).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Sperm motility behaviors were robust, as little variability was seen across samples from three different bulls. We reported in a previous publication that the chiral trajectories are caused by the near-surface resistive force exerted on the sperm head (11). Chiral swimming trajectories are characteristics of all near-surface pusher microswimmers (16,17).…”
Section: Resultsmentioning
confidence: 86%
“…Our work demonstrated that sperm upstream swimming is governed by near-surface hydrodynamic interaction, via the interactions of a front-back asymmetric microswimmer with a solid boundary. Therefore, when sperm are far away from a solid surface, there will be no force that orients them upstream (11). Moreover, the upstream swimming is governed by hydrodynamic bifurcation theory, which applies to a broad class of microswimmers that swim close to a surface and in a chiral trajectory (11).…”
Section: Sperm Swam Against a Gentle Flow Whereas T Foetus Were Sweptmentioning
confidence: 99%
See 2 more Smart Citations
“…3E). The two distinct turning behaviors can then be inferred from basic force balance considerations (32,33,62): Approximating the flagellar beat envelope by a cone rotating counterclockwise around its symmetry axis, hydrodynamic interactions with the wall effectively result in a left-turning torque (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%